A Crystat for Determinations of the Latent Heat of Liquid Helium - Roeder, Robert (My University, 1960)
A cryostat has been constructed for the determination of latent heat of vaporization of liquid helium at temperatures from the critical temperature (5.2°K) to below the A point (2.2°K). Some details of the apparatus, hints on low temperature technique and suggestions for future equipment are presented, together with results of some experiments on the apparatus.
Keywords: cryostat; latent heat; liquid helium